An inclusive and participatory approach to changing policies and practices for improved milk safety in Assam, northeast India - Lindahl, Johanna F.; Deka, Ram Pratim; Melin, David; Berg, Anna; Lundén, Hanna; Lapar, Ma. Lucila; Asse, Rainer; Grace, Delia (Elsevier, 2018)
Animal products are highly nutritious, but also highly perishable. In India milk is an important source of animal protein, but problems with low quality of the milk, high degrees of adulterated milk on the market, high bacterial loads, and sometimes presence of zoonotic pathogens persist. Most dairy farmers in India are resource-poor small-holders, often with limited knowledge about the importance of food safety and hygiene. Milk quality problems including adulteration and bacterial contamination is common in the country. This paper describes a training intervention for improved food safety in Guwahati, Assam, India, conducted in 2009–2013. The training was designed to be short, simple and customized, cheap to deliver, easily accessible, and accompanied by incentives to bring change in knowledge, attitude and practices (KAP). In 2014 three outcomes were assessed: changed KAP; milk production; and, mastitis prevalence. Selected food safety hazards were also assessed, although their management had not been included in training. We found evidence of improved KAP among trained farmers, 14% higher milk production, and a tendency towards less mastitis, but no effects on food safety hazard levels. This study shows that a training intervention can have a medium-term impact, while the issue of food safety is more complex and cannot be assumed to automatically follow from even successful training.